Raising children in the military - Lawhorne Scott, Cheryl 1968-; Philpott, Don 1946-; Scott, Jeff 1969- (Military life (Lanham, Md.), 2014)
Military life places unique demands on military families with children including frequent moves, disruptions in schooling, family separation, health care issues, loss of friends, financial hardships, underemployment of military spouses, and the ever present threat of risk of injury or death of loved ones deployed. But learning how to navigate these challenges can help prepare families for those events as they arise. Here, the authors have assembled information about common problem areas and have included detailed information about solutions and resources available. The information in this guide has been carefully gathered from hundreds of sources and resources and includes the most up to date information about child services and benefits from the Department of Veterans Affairs, allowing serving members of the military with children to quickly access information that they need regarding all aspects of child care, from raising a family to education, and from coping with constant moves to grief counseling. It also covers other critical issues such as wellness, family solidarity, benefits, insurance and problems such as addiction and domestic violence. Readers will gain a better understanding of what child services and benefits are available and how to obtain them as well as secrets for successful relationships and family bonding.